Genomic characterization of psittacine adenovirus 2, a siadenovirus identified in a moribund African grey parrot (Psittacus erithacus) - Surphlis, Austin C.; Dill-Okubo, Jennifer A.; Harrach, Balázs; Waltzek, Thomas; Subramaniam, Kuttichantran (Archives of virology, 2022)
Here, we report the complete genome sequence of psittacine adenovirus 2 from a moribund African grey parrot ( Psittacus erithacus ) with neurological signs and systemic inflammation. The complete siadenovirus genome is 25,386 bp in size. The results of genetic and phylogenetic analyses support its classification as a member of a novel species within the genus Siadenovirus . This study represents the first report of the genome sequence of an adenovirus from an African grey parrot.